Multidrug resistance of DNA-mediated transformants is linked to transfer of the human mdr1 gene. - Shen, D W (1986)
Mouse NIH 3T3 cells were transformed to multidrug resistance with high-molecular-weight DNA from multidrug-resistant human KB carcinoma cells. The patterns of cross resistance to colchicine, vinblastine, and doxorubicin hydrochloride (Adriamycin; Adria Laboratories Inc.) of the human donor cell line and mouse recipients were similar. The multidrug-resistant human donor cell line contains amplified sequences of the mdr1 gene which are expressed at high levels. Both primary and secondary NIH 3T3 transformants contained and expressed these amplified human mdr1 sequences. Amplification and expression of the human mdr1 sequences and amplification of cotransferred human Alu sequences in the mouse cells correlated with the degree of multidrug resistance. These data suggest that the mdr1 gene is likely to be responsible for multidrug resistance in cultured cells.